2006
DOI: 10.1248/jhs.52.774
|View full text |Cite
|
Sign up to set email alerts
|

The Pyrethroid Cypermethrin-Induced Biochemical and Histological Alterations in Rat Liver

Abstract: Cypermethrin, a synthetic pyrethroid, has broadspectrum use in agriculture, domestic and veterinary applications due to its high bioefficacy, enhanced stability and considerably low mammalian toxicity. The objective of this study was to investigate the cypermetrin-induced alterations in the liver tissue of Wistar male rats, based on the histopatological, enzymological analyses and apoptotic changes. The animals of the experimental groups were orally fed with laboratory chow combined 60, 150, and 300 mg/kg Kral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 28 publications
5
18
3
Order By: Relevance
“…Our results are in agreement with Chao et al (2009) who reported that AChE activity was significantly inhibited in both brain and muscle samples of juvenile goldfish exposed to propoxur (alone, in a binary mixture with isoprocarb, and in a ternary mixture with isoprocarb and chlorpyrifos). However, the significant decrease of AChE activity recorded in our results contradict those recoded by Yavasoglu et al (2006) who showed that liver AChE activities increase in rats treated with cypermethrin compared with control values but these inductions were not statistically significant. Letters mean the significant differences between treatments according to Duncan's test; Each figure between brackets represents the percentage of content as check; GOT -Glutamic Oxaloacetic Transaminase; GPT -Glutamic Pyruvic Transaminase Unauthenticated Download Date | 5/9/18 5:22 AM…”
Section: Enzymatic Studiescontrasting
confidence: 99%
“…Our results are in agreement with Chao et al (2009) who reported that AChE activity was significantly inhibited in both brain and muscle samples of juvenile goldfish exposed to propoxur (alone, in a binary mixture with isoprocarb, and in a ternary mixture with isoprocarb and chlorpyrifos). However, the significant decrease of AChE activity recorded in our results contradict those recoded by Yavasoglu et al (2006) who showed that liver AChE activities increase in rats treated with cypermethrin compared with control values but these inductions were not statistically significant. Letters mean the significant differences between treatments according to Duncan's test; Each figure between brackets represents the percentage of content as check; GOT -Glutamic Oxaloacetic Transaminase; GPT -Glutamic Pyruvic Transaminase Unauthenticated Download Date | 5/9/18 5:22 AM…”
Section: Enzymatic Studiescontrasting
confidence: 99%
“…Regarding the relative liver weight, Aldana et al (5) reported a 20% increase in the 7-day CYP toxicity study. However, there were no significant changes in relative liver weights in a 28-day CYP toxicity study (6). In the present study, there were no significant differences in relative liver weight among the groups.…”
Section: Discussioncontrasting
confidence: 69%
“…There is an increasing amount of evidence suggesting toxic effects on nontarget organisms in chronic exposure of CYP (5,6). Several studies have shown that CYP causes oxidative stress, biochemical changes such as increase in activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and lactate dehydrogenase (LDH); elevation in levels of thiobarbituric acid reactive substances (TBARS), a decrease in activities of the antioxidant enzymes (7,8), and histopathological changes such as vacuolar degeneration, enlarged sinusoid, vacuole formation in hepatocytes, pleomorphism in the nucleus, congestion, necrosis, hepatocellular hypertrophy, multinucleated hepatocytes, mononuclear cell infiltration (MCI), and increase in Kupffer cell numbers (2,6). Marijuana or cannabis, whose main active ingredient is delta-9-tetrahydrocannabinol, activates two G proteincoupled membrane receptors, named CB1 and CB2 (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The dosedependent effect of cypermethrin on the biochemical and histological indexes leading to various pathological conditions is widely studied [10,9,36]. However, the dose selected for this study is based on the dose-dependent study conducted in our laboratory [31].…”
Section: Animal Treatmentmentioning
confidence: 99%